Crystallographic and topographic analysis of ultra-translucent zirconia after various surface treatments = Análisis cristalográfico y topográfico de la zirconia ultra-translúcida después de diversos tratamientos de superficie - Vargas Koudriavtsev, Tatiana 1980-
The aim of the present study was to analyze the effects of 4 different surface treatments, on the crystallographic characteristics of Ultra-Translucent Zirconia. Fully sintered zirconia specimens of highly translucent yttria partially stabilized zirconia (Y-PSZ) (KATANA UTML) were divided into four experimental groups and a control group (n=10). Each group received one of the following surface treatments: sandblasting with 50μm alumina particles (Al2O3), sandblasting with 110μm alumina particles, and grinding with a rotary high-speed turbine with and without water irrigation. For each sample, x-ray diffraction was carried out to analyze peak intensity, calculate the crystallite size, and detect the presence of compressive and tensile stress. Surface roughness was measured on all specimens using a standard scanning profilometer. Additionally, scanning electron microscopy (SEM) was performed to qualitatively analyze the surfaces of the specimens. Statistical analysis included repeated measures analysis of variance and post hoc Tukey test (p≤0.05). The control group exhibited the highest crystallite size (323nm). All surface treatments led to a reduction in the crystallite size, with the most significant reduction observed in the groups subjected to sandblasting with 110μm alumina particles and high-speed grinding with irrigation. Sandblasting with 50μm alumina particles resulted in less transformation of the crystallite size. A general tendency of the diffraction peaks to shift to a lower angle can be observed in the experimental groups, indicating the presence of compressive stress on the samples. Profilometry revealed higher roughness in the ground samples (6,14μm and 6,57μm) compared to the sandblasted groups (2,93μm and 2,02μm). The crystal domain size showed a tendency to decrease after the surface treatments. Sandblasted samples, as well as ground samples without irrigation, exhibited compressive stress. Sandblasted samples had lower...